CLINICAL SAFETY OF FOCUSED ULTRASOUND SURGERY IN THE TREATMENT OF ADVANCED PANCREATIC CANCER PATIENTS - SINGLE CENTER PROSPECTIVE STUDY - Dobromir Dimitrov; Martin Karamanliev; Nadya Stanislavova; Hyulia Feradova; Yoana Ivanova-Yoncheva; Tsanko Yotsov; Vasil Neykov; Kun Zhou; Grigor Gorchev; Tsvetomir Ivanov; Slavcho Tomov (Peytchinski Publishing, 2019)
Purpose: Our purpose is to study the clinical safety of focused ultrasound surgery (FUS) in the treatment of patients with advanced pancreatic cancer. Methods: A single-center prospective study was conducted in the period 02. 2013 - 06. 2018 at HIFU department at University hospital St. Marina - Pleven, Bulgaria looking at the postoperative complications after focused ultrasound surgery of advanced pancreatic cancer patients. Results: 47 patients were included in the study with a III or IV stage pancreatic cancer. The complication rate was 10.6% and no severe complications were observed. Conclusions: FUS seems to be a safe method of treating patients with advanced pancreatic cancer. Large randomized trials in the area are needed.